Adrenergic hypersensitivity after beta-blocker withdrawal. Issue 6 (June 1981) - Ross, P J; Lewis, M J; Sheridan, D J; Henderson, A H
Abstract : We investigated the possibility of a rebound increase in sympathetic response after stopping beta-blocker treatment by measuring heart rate under conditions of increased sympathetic drive, as provided by standing with vasodilatation, or the Valsalva manoeuvure. Significant rebound increases in heart rate were observed after stopping propranolol given for one or more weeks but not when given for only four days. The amplitude of the rebound heart rate relative to the control heart rate off beta-blockers was similar after propranolol, atenolol, oxprenolol, or acebutolol, and in hyperthyroid subjects.